84.1k views
16 votes
What is the answer to -2/3 ÷ (-1/6) in simplest form ?

User Eivind
by
4.9k points

2 Answers

8 votes

Answer:

4

Explanation:

Since you can't divide a fraction by another fraction, you start by flipping the second fraction (-1/6 becomes -6/1) and changing the division sign to multiplication.

-2/3 x -6/1

Multiply across, numerator with numerator and denominator with denominator. Also, when multiplying or dividing negative numbers, two negatives make a positive (i.e. -2 x -6 = +12)

-2/3 x -6/1 = 12/3

12/3 = 4

User Carpy
by
4.8k points
4 votes

Answer: 4

Explanation:

=( −2 /3)( −1 /6)

=( −2 /3 )( 6 /−1 )

= (−2)(6)/ (3)(−1)

= −12 /−3

=4

User Longchiwen
by
4.6k points